Leadership Development for Department Chairs: Learnings Across Three Approaches - Emily R. Smith; Patricia E. Calderwood; Paula Gill Lopez; Ryan Colwell (Academic Chairpersons Conference Proceedings, 2017)
This session shares insights and recommendations from three approaches to faculty leadership development: a co-mentoring group for faculty leaders; a community of practice for mentoring; and a leadership development cohort. Participants will be invited assess and revise these recommendations to jointly inform best practices in faculty leadership development.
Keywords: Leadership development; co-mentoring; community of practice; chairs; cohort